PHARMACOLOGICAL CORRECTION OF CEREBRAL BLOOD FLOW DISTURBANCES IN WOMEN WITH ARTERIAL HYPERTENSION IN POSTMENOPAUSE - V. V. Yakusevich; M. E. Mozheiko; N. V. Sudareva; N. E. Semyonova (Столичная издательская компания, 2015)
Aim: to study cerebral blood flow and cholesterol metabolism in menopausal women with arterial hypertension (AH); to evaluate dynamics of cerebral blood flow parameters and plasma lipid concentrations in these patients during 6-month antihypertensive and hypolipidemic therapy. Material and methods: 24 women with AH of I and II grade were examined. They were in postmenopausal period of life during 7,1±0,5 years. At the beginning of the study all women were prescribed moexipril as monotherapy, daily dose 7,5 - 15 mg. Patients with initial dislipidemia were prescribed lipid reducing drug atorvastatin in 10mg daily dose additionally to the antihypertensive therapy. Therefore all the patients were divided into two groups: I - monoteraphy with moexipril (13 people), II - combined therapy with moexipril and atorvastatin (11 people). At the beginning of the study and after 6 months all the patients passed through ultrasonic Dopplerography of vessels of head and neck, rheoencephalography, their lipoproteidogrammes were studied. Results: During 6-month therapy all the patients showed proved decrease in systolic and diastolic blood pressure, also positive dynamics of neuropsychological status, improvement in cerebral blood flow according to the results of Dopplerography of vessels and rheoencephalography. Normalization of plasma lipid spectrum was noted. More significant positive changes in cerebral hemodynamic parameters and plasma lipid spectrum were observed in patients, who received combined therapy with antihypertensive and lipid reducing drugs. Conclusion: Deterioration of cerebral hemodynamics is typical for women with long-lasting AH. The most positive influence on cerebral perfusion was received due to combined therapy with moexipril and atorvastatin.